2023
DOI: 10.1002/advs.202205289
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome Dynamically Associates with Host Glucose Metabolism throughout Pregnancy: Longitudinal Findings from a Matched Case‐Control Study of Gestational Diabetes Mellitus

Abstract: Though gut microbiome disturbance may be involved in the etiology of gestational diabetes mellitus (GDM), data on the gut microbiome's dynamic change during pregnancy and associations with gestational glucose metabolism are still inadequate. In this prospective study comprising 120 pairs of GDM patients and matched pregnant controls, a decrease in the diversity of gut microbial species and changes in the microbial community composition with advancing gestation are found in controls, while no such trends are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…A high-fiber diet is believed to increase SCFA levels and improve human health [ 66 ]. A recent study involving 120 pairs of GDM women and matched controls from the first trimester to the third trimester indicated that the healthy status of women suffering from GDM was modified with the intake of a high-fiber diet [ 25 ]. Parallel changes in the gut microbiome, including Escherichia coli , Fusobacterium mortiferum , Bacteroides massiliensis , and Bifidobacterium dentium , were also observed [ 25 ].…”
Section: Impact Of Lifestyle On Gut Microbiome and Reproductive Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…A high-fiber diet is believed to increase SCFA levels and improve human health [ 66 ]. A recent study involving 120 pairs of GDM women and matched controls from the first trimester to the third trimester indicated that the healthy status of women suffering from GDM was modified with the intake of a high-fiber diet [ 25 ]. Parallel changes in the gut microbiome, including Escherichia coli , Fusobacterium mortiferum , Bacteroides massiliensis , and Bifidobacterium dentium , were also observed [ 25 ].…”
Section: Impact Of Lifestyle On Gut Microbiome and Reproductive Healthmentioning
confidence: 99%
“…Studies indicated that the increase of Enterobacteriaceae, Streptococcus , and Lactobacillus , as well as high levels of insulin insensitivity and blood glucose, helps mothers harvest more energy, thus supporting the growth of fetuses [ 172 , 177 ]. Nevertheless, an unhealthy lifestyle during pregnancy disturbs the maternal microbiome, which is associated with poor maternal conditions and leads to the occurrence of pregnancy complications, further influencing the development of infants [ 13 , 25 , 26 , 175 ].…”
Section: Microbial Biomarkers and Pregnant Complicationsmentioning
confidence: 99%
See 3 more Smart Citations